Fingerprint As A Means of Identification In The Crime Of Murder (Study At Polresta Pematang Siantar) - Putri Sari Tampubolon (Institute Of computer Science (IOCS), 2020)
The crime of murder is currently one of the most complicated and very serious problems faced by individuals, society, law enforcement, and the government. The impact of this act of killing was felt very strongly by the community, namely the disruption of security and order in society. Therefore, this crime of murder needs to be handled or tackled seriously. It is in this part of the investigation that the Police can take the first step, namely managing the crime scene (TKP) by identifying any evidence found such as objects that are strongly suspected of being related to the incident, including the victim, objects around the victim or in the vicinity of the victim. around the crime scene. And for the purposes of investigation, the Police are authorized or entitled to take several actions that have been regulated or determined by the Law on the Indonesian National Police No. 2 of 2002 in Article 15 paragraph (1), including taking fingerprints and other identities and taking pictures of someone. This is the reason behind the author's interest in writing a thesis with problems including: How is the process of formulating fingerprints (dactyloscopy) in identifying a crime of murder; What is the role of fingerprints as a means of identification in a murder crime and what are the obstacles faced in the process of identifying a murder crime by using fingerprints as a means of identification. The research used in this thesis is a normative juridical research method which in research the author generally uses library materials or secondary data as basic data materials in research activities. Through this thesis, it is hoped that it can provide input for law enforcement officers, especially the POLRI in uncovering the crime of murder through fingerprints as a means of identification. Regarding the realization of the recognition and protection of one's right to life, this is a very serious matter because, as stated earlier, this right is the most essential right for every human being. However, recently, more and more problems have been faced with regard to the realization of this right to life, among which the most common is the deprivation of the right to life. Deprivation of the right to life that we usually or often encounter is by coercion and violence which is generally known in our society as an act of murder or a crime of murder. However, recently, more and more problems have been faced with regard to the realization of this right to life, among which the most common is the deprivation of the right to life. Deprivation of the right to life that we usually or often encounter is by coercion and violence which is generally known in our society as an act of murder or a crime of murder. However, recently, more and more problems have been faced with regard to the realization of this right to life, among which the most common is the deprivation of the right to life. Deprivation of the right to life that we usually or often encounter is by coercion and violence which is generally known in our society as an act of murder or a crime of murder.